Assessing vibratory stimulation-induced cortical activity during a motor task—A randomized clinical study. (3rd November 2015) - de Moraes Silva, Janaína; Lima, Fernanda Pupio Silva; de Paula Júnior, Alderico Rodrigues; Teixeira, Silmar; do Vale Bastos, Victor Hugo; dos Santos, Rayele Pricila Moreira; de Oliveira Marques, Charlanne; da Conceição Barros Oliveira, Maria; de Sousa, Felipe Aurélio Nunes; Lima, Mario Oliveira
Highlights: Evaluation of the vibration therapy effect on cortical dynamics is proposed. The vibratory stimulation causes a variability in cortical activation. Beta band alteration was found both in the ipsi-lateral and contra-lateral cortexes. Abstract: Effects of vibratory stimulation on motor performance have been widely investigated. Many theories have been applied, in order to evaluate its influence on individuals; however, very few studies have researched vibratory stimulation-induced cortical behavior. The aim of the present study is to investigate behavioral changes, such as reaction time and index finger movements, as well as electrophysiological changes, using beta band absolute power, in subjects submitted to vibratory stimulation. For this study, 30 healthy subjects were randomly selected and divided into two groups, experimental and control, and were submitted to a right index finger task, before and after vibratory stimulation, which was applied to the right upper limb, while their standard cerebral activity was recorded through electroencephalogram. No significant difference was found among behavioral variables. On the other hand, beta band absolute power significantly increased in the experimental group for the C3, C4 and P4 derivations, while it decreased at P3. The results suggest that electrophysiological changes were induced by vibratory stimulation, while reaction time and task-related movements were not affected by it.